Syllids inhabiting holdfasts of Lessonia spicata in Central Chile: diversity, systematics, and description of three new species. Issue 6 (2nd November 2017) - Álvarez-Campos, Patricia; Verdes, Aida
Abstract : The diversity of syllid polychaetes inhabiting holdfasts of the brown algae Lessonia spicata in Central Chile was investigated. We found 12 species, belonging to the genera Syllis, Amblyosyllis, Proceraea and Salvatoria within the internal cavities of 14 holdfasts collected from the intertidal and subtidal zones of exposed rocky shores. This is the first record of syllid polychaetes living in association with the kelp L. spicata . In addition, we provide the descriptions of three new species, Syllis albae sp. nov., Syllis tamarae sp. nov. and Syllis tripantu sp. nov. discovered from the holdfast faunal assemblage. We describe their phylogenetic position and evolutionary relationships with other species within the genus Syllis, which were evaluated by phylogenetic analyses. Additionally, we provide new biogeographic information and ecological data, including updated distribution limits and habitat preferences for all identified species. This study highlights the importance of kelp holdfasts as hotspots of syllid diversity and suggests the potential use of associated Syllidae assemblages as tools for monitoring changes in the marine ecosystem that affect species distribution. http://zoobank.org/References/EE82D79E-1C24-4807-BBC7-C3BCBE343A47 http://zoobank.org/urn:lsid:zoobank.org:act:93832177-4F4D-4BF1-925D-AC6DD7EE72CD http://zoobank.org/urn:lsid:zoobank.org:act:74E5DCF6-6D4E-4B00-ABF9-EA4E82408A26 http://zoobank.org/urn:lsid:zoobank.org:act:7CAB9F72-7577-4C8F-AE03-093874603F67